2014
DOI: 10.5901/mjss.2014.v5n2p103
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Foundation Phase Teachers in Implementing the Curriculum

Abstract: This article seeks to explore experiences of foundation phase teachers in rural schools

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
0
13
1
2
Order By: Relevance
“…Nenty et al (2007) and Hwa and Lim (2008) highlighted that assessment plays a major role in mathematics education. One of the factors which influence the effectiveness of assessment is the understanding and knowledge of teachers on how assessment being carried out in the education system (Makeleni & Sethusha, 2014;Rasidayanty, 2014). Rasidayanty (2014); Makeleni and Sethusha (2014), argue that teachers need proper programme and training to enhance their knowledge on assessment to improve assessment in schools and classrooms.…”
Section: Level Of Knowledge and Practice Of The Teachers From The Aspmentioning
confidence: 99%
See 1 more Smart Citation
“…Nenty et al (2007) and Hwa and Lim (2008) highlighted that assessment plays a major role in mathematics education. One of the factors which influence the effectiveness of assessment is the understanding and knowledge of teachers on how assessment being carried out in the education system (Makeleni & Sethusha, 2014;Rasidayanty, 2014). Rasidayanty (2014); Makeleni and Sethusha (2014), argue that teachers need proper programme and training to enhance their knowledge on assessment to improve assessment in schools and classrooms.…”
Section: Level Of Knowledge and Practice Of The Teachers From The Aspmentioning
confidence: 99%
“…One of the factors which influence the effectiveness of assessment is the understanding and knowledge of teachers on how assessment being carried out in the education system (Makeleni & Sethusha, 2014;Rasidayanty, 2014). Rasidayanty (2014); Makeleni and Sethusha (2014), argue that teachers need proper programme and training to enhance their knowledge on assessment to improve assessment in schools and classrooms. Every teacher needs in-depth knowledge and skills to assess students in accordance with the specific strategy that is only appropriate for assessing specific objective (Hammond, 2006).…”
Section: Level Of Knowledge and Practice Of The Teachers From The Aspmentioning
confidence: 99%
“…Pakar-pakar kurikulum menyarankan adanya monitoring dan evaluasi. Pada implementasi kurikulum, guru sebaiknya dimonitor dan didukung agar fokus pada kualitas pembelajaran (Makeleni & Sethusa, 2014). Hasil monitoring ini dapat dijadikan bahan untuk perbaikan pelaksanaan kurikulum dan juga proses pengembangan kurikulum (Hussain, Adeeb, Aslam, 2011).…”
unclassified
“…From the explanation above, it can be seen that there are many factors influence the implementation of authentic assessment like the basic training teachers received, lack of curriculum interpretation, inadequate resources, poor infrastructure, and overcrowding (Makeleny et al, 2014). They found that the basic training affected teachers' knowledge and understanding of curriculum principles, instructional planning, teaching and learning, and assessment practices in that some teachers were unable to meet the requirements of curriculum implementation.…”
Section: Discussionmentioning
confidence: 99%